Inter-Governmental Conflicts between Spain and Catalonia - Jean-Baptiste Harguindéguy (Revista Española de Investigaciones Sociológicas (REIS), 2017)
This paper focuses on tensions between the governments of Catalonia and Spain, using as a proxy the number of instances of litigations per year between these two bodies brought before the Constitutional Court between 1984 and 2014. On the one hand, descriptive statistics demonstrate that Catalonia is the most conflictive region in Spain. On the other hand, inferential statistics indicate that periods of absolute majority in the Spanish Parliament, the presence of a nationalist government in Catalonia, and funding problems of the Catalan Government tend to increase the number of inter-governmental conflicts with the Spanish Government.